Experimental and theoretical study on the performance of semi-transparent photovoltaic glazing façade under shaded conditions. (15th September 2020) - Wu, Jing; Zhang, Ling; Liu, Zhongbing; Luo, Yongqiang; Wu, Zhenghong; Wang, Pengcheng
Abstract: Semi-transparent photovoltaic glazing (STPVG) façade is a promising curtain wall system, which not only has the function of traditional glazing façade but also can use solar energy to generate electricity. However, STPVG is often working under building shadow, and it will make power output loss for building. In this paper, the power performance of STPVG under the influence of building shadow is studied. Firstly, a real-time building shadow model that changes with time and space is established. Then a model of STPVG under the shadow is established. An experimental test platform for STPVG was built, and the model was verified using experimental data. The simulation results agree well with the experimental results. On this basis, the model is used to simulate the annual power generation performance of the STPVG under the influence of the building eave shadow. The results show that a small eave shadow will cause a certain decrease in the power output of the STPVG system. The annual average of the irradiation reception loss rate caused by eaves shadow is 0.286%, while the average rate of decline in energy generation is 3.92%. This study provides a theoretical basis for the application and optimization of STPVG in buildings. Highlights: The photoelectric model of the STPVG under the building shadow is established. An experimental test platform was built and the data were used to verify the model. The annual power performance of the STPVG under the eave shadow is simulated. A small shadow will cause a sharp decrease in the power generation of the STPVG.